"We have it, we sit on it" : a formative evaluation of a high school sexuality education programme - Bailie, Ross Stewart (Department of Paediatrics and Child Health, 2018)
This dissertation reports on a formative evaluation of a high school sexuality education programme. The evaluation aimed to generate a greater understanding of pupils' attitudes to sexuality and insight into pupils' responses to a sexuality education programme. A qualitative method using focus groups was used. The groups comprised pupils, with programme staff acting as facilitators and observers. The foremost findings were that pupils had considerable understanding of many of the issues which the programme aims to teach them about. Pupils requested that the programme address issues of their concern, including lifeskills development. They expressed dislike of lectures, and requested the use of small group discussions. They also expressed the need for individual counselling under circumstances where the pupils could develop a trusting relationship with the counsellor. Pupils expressed difficulty communicating with their parents about sexuality, and distrust for their teachers in the role of counsellors or educators in this field. In conclusion, the evaluation yielded much information of potential use in development of the sexuality education programme, and recommendations are put forward. By basing a Family Planning Advisor at each school the pupils needs could be better addressed. Such an arrangement would allow the advisor to encourage parents and the wider community to participate in the programme. This type of broad approach appears to be a prerequisite for success in this field.